KNOWLEDGE AND PRACTICES OF PREVENTION AND CONTROL OF NEEDLE STICK INJURIES AMONG NURSES AND MEDICAL OFFICERS AT WAKISO HEALTH CENTER IV, A CROSS-SECTIONAL STUDY. - Musana, Patricia; Nansereko, Hasifa; Tubenawe, Martha; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2025)
Background Healthcare workers are at a high risk of accidental needle stick injuries because many are unaware or fail to adhere to set guidelines on infection control, which may often result in injury and blood-borne infections. The purpose of this study was, therefore, to assess the knowledge and practices of prevention and control of needle stick injuries among nurses and medical officers at Wakiso Health Center IV, Wakiso District. Methodology A cross-sectional study design was used to collect quantitative data using a semi-structured questionnaire. Participants were picked to participate randomly using a simple random sampling method, from which 30 participants enrolled and consented to take part in the study. Results Results from the data collection showed a response rate of 100%, and the results showed most participants were in the age groups of 18-45 years. 83.3% of nurses and medical officers were aware that blood-borne infections can be transmitted by needle-stick injuries. 93.3% had heard of needle stick injuries among health workers. 70% were of the impression that syringes and needles should be discarded in a sharp box being used. 60% of the injuries had occurred due to poor disposal of sharps, while 23.3% were due to poor organization in the areas of work. Conclusion In conclusion, this research revealed that most healthcare workers had adequate knowledge about the preventive measures and associated risks of needle-stick injuries. However, practices needed to be improved. Recommendation I, therefore, recommend that continuous onsite training should be done for the prevention and reporting of needle stick injuries. I also further recommend better management of healthcare workers who have sustained needle injuries.